BIOM-09. MYO-INOSITOL LEVELS ON MR SPECTROSCOPY CAN PREDICT FAILURE OF ANTI-ANGIOGENIC TREATMENT IN RECURRENT GLIOBLASTOMA. (12th November 2021) - El-Abtah, Mohamed; Wenke, Michael; Talati, Pratik; Fu, Melanie; Kim, Daniel; Weerasekera, Akila; He, Julian; Vaynrub, Anna; Vangel, Mark; Rapalino, Otto; Andronesi, Ovidiu; Arrillaga-Romany, Isabel; et al.
Abstract: BACKGROUND: Recurrent glioblastoma (rGBM) patients are often treated with anti-angiogenic agents such as bevacizumab (BEV). Despite therapeutic promise, conventional MR methods fail to determine which patients may not benefit. PURPOSE: The purpose of this study was to utilize magnetic resonance spectroscopic imaging (MRSI) with intermediate and short echo time to generate corrected Myo-inositol normalized by contralateral creatine (mI/c-Cr) in patients with rGBM treated with BEV and investigate whether it can predict survivorship prior to BEV initiation (baseline) and at 1-day, 4-weeks, and 8-weeks thereafter. METHODS: We conducted a prospective, longitudinal study and evaluated spectroscopic data of myo-inositol (mI), a glial marker and osmoregulator within the brain, normalized to contralateral-creatine (mI/c-Cr) in the intratumoral, contralateral normal appearing white matter, and peritumoral volumes of rGBM patients. Area under the ROC curve (AUC) was calculated for all volumes at baseline, 1-day, 4-weeks, and 8-weeks after treatment to determine mI/c-Cr's ability to predict survivorship. RESULTS: 21 participants (62 ± 12 years, 15 men) were evaluated. Lower mI/c-Cr in the tumor prior to and during BEV treatment predicted poor survivorship, with ROC analyses illustrating an AUC of 0.75 at baseline, 0.87 at 1-day, and 1 at 8 weeks. Lower levels of mI/c-Cr were also observed in the contralateral and the peritumoral volumes for shorter-term survivors. In the contralateral volume, lower mI/Cr was predictive of shorter-term survival at baseline and all other timepoints. Within the peritumoral volume, lower mI/c-Cr was predictive of shorter-term survival at baseline (AUC=0.80), 1-day (AUC=0.93), and 4-weeks (AUC=0.68). CONCLUSIONS: Lower levels of mI/c-Cr within intratumoral, contralateral, and peritumoral volumes were predictive of poor survivorship and anti-angiogenic treatment failure as early as one month before BEV treatment. Acquiring MRSI alongside conventional MR imaging modalities can convey critical information regarding tumor microenvironment that informs management of patients with rGBM.